2005
DOI: 10.1677/joe.1.06030
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular effects of corticotropin-releasing hormone in human skin vary in relation to estrogen concentration during the menstrual cycle

Abstract: Females have a significantly greater life expectancy than males, which in part may be due to the cardio-protective effects of the female sex hormone, estrogen, on vascular function. However, the sex-specific mechanisms contributing to these differences are complex and not fully understood. Previously we have reported that corticotropin-releasing hormone (CRH) has potent dilator effects in the female skin circulation via mast cell degranulation. Furthermore the dilator response to CRH was more enhanced in femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
1
7
2
Order By: Relevance
“…However, at the microcirculatory level, it has been recently shown that the menstrual cycle had no effect on skin endothelial vasodilation tested with ACh iontophoresis (9). In our study, there is no statistical difference in the phase of the cycle between BDC-7 and HDT ϩ 56.…”
Section: Discussioncontrasting
confidence: 66%
“…However, at the microcirculatory level, it has been recently shown that the menstrual cycle had no effect on skin endothelial vasodilation tested with ACh iontophoresis (9). In our study, there is no statistical difference in the phase of the cycle between BDC-7 and HDT ϩ 56.…”
Section: Discussioncontrasting
confidence: 66%
“…However, findings on the impact of hormone levels such as serum oestradiol on PORH in microcirculation are inconsistent [45,46]. Regarding the proportion of female study participants in both groups, a subgroup analysis addressing the stages of the menstrual cycle would have considerably lowered the statistical power of our study.…”
Section: Discussionmentioning
confidence: 88%
“…CRH can also modify DNA synthesis in the dermal and epidermal compartments of cultured mouse skin depending on the phase of the hair growth cycle (24). These differential effects are apparently related to fluctuations in CRH-R1 and CRH-R2 expression during the hair growth cycle (20,24,65) Skin vasculature is a recognized target for CRH and urocortin peptides (6,(77)(78)(79), where, depending on the animal model used, CRH can induce local vascular dilatation (6,(77)(78)(79) and either inhibit or stimulate angiogenesis (80,81). Interestingly, both CRH and urocortin demonstrated anti-edema effects (82)(83)(84).…”
Section: Phenotypic Effects Of Crh and Urocortin In Cultured Skin Cellsmentioning
confidence: 99%
“…In the specific case of human skin, Clifton et al clearly have shown vasodilatory action of CRH, mediated by mechanisms that included both indirect effects, activation of mast cells or endothelial-dependent pathways, and a direct action on the blood vessel wall (77)(78)(79). These vascular effects of CRH appear to be dependent on the local level of estrogenization (77).…”
Section: Phenotypic Effects Of Crh and Urocortin In Cultured Skin Cellsmentioning
confidence: 99%